Geochemical Characteristics of Organic Matter from Maikop Rocks of Eastern Azerbaijan - Guliyev, I.S.; Tagiyev, V.F.; Feyzullayev, A.A. (My University, 2001)
Based on investigation of more than 170 samples taken from natural outcrops of the Maikop Formation (Oligocene–Lower Miocene) in eastern Azerbaijan, the genetic hydrocarbon potential and the organic matter (OM) maturity of these rocks were estimated. In the study region, sedimentary rocks of this formation were deposited under reductive or weakly oxidative conditions. Possessing a relatively high (1.9%, on the aver- age) content of organic matter of a mixed (continental–marine) OM, these rocks are able to generate both liquid and gaseous hydrocarbons under favorable conditions. Contributions of both the continental and marine components to the total organic carbon (TOC) varied in time and space. The upper and lower subformations of the Maikop Formation differ in the qualitative and quantitative compositions of OM. Oligocene rocks have a relatively lower OM content and are characterized by better oil-generating properties, as compared to lower Miocene rocks.
Keywords: geochemistry; Maikop Rocks; Azerbaijan